Pengaruh Kepemimpinan Transformasional Kepala Sekolah terhadap Kinerja Guru - Sugianto, Endrik (Lembaga Yasin AlSys, 2024)
This study aims to analyze the effect of principal transformational leadership on teacher performance. Methods used are literature reviews. Transformational leadership is measured based on four main dimensions: charisma, inspiration, intellectual stimulation, and individualized consideration. Teacher performance was measured using indicators of attendance, teaching quality, professional development, and involvement in school activities. The regression analysis results show that principals’ transformational leadership has a positive and significant influence on teacher performance. Of the four dimensions of transformational leadership, the charisma and inspiration dimensions have the strongest influence on improving teacher performance. This study also found that intellectual stimulation and individualized consideration also contributed significantly, although on a smaller scale. The implication of these findings is that it is important for principals to apply transformational leadership style to improve teachers’ motivation and performance. Principals are advised to develop their leadership skills through training and self-development programs that focus on transformational aspects. Thus, it is expected that the quality of education in schools can be continuously improved.